Burden of smoking-related stroke in Saudi Arabia: trends from 1990 to 2021. - Jaber S Alqahtani; Ibrahim A AlDraiwiesh; Abdulelah M Aldhahir; Tope Oyelade (PLoS ONE)
Background Stroke ranks among the top causes of death and disability globally, with smoking being a significant risk factor for its development. This study aims to assess the impact of smoking-related strokes in Saudi Arabia from 1990 to 2021. Methods The data was extracted from the Global Burden of Disease (GBD) 2021 database. We assessed the burden of smoking-related stroke by estimating the age-standardized rate (ASR) of years of life lost (YLLs), years lived with disability (YLDs), disability-adjusted life years (DALYs) and deaths related to this disease. Results From 1990 to 2021, there was a respective 22.37% and 24.15% absolute decrease in the ASR of DALYs and ASR of YLLs, with average annual percentage changes (AAPCs) of -0.85 (-0.88, -0.83) and -0.92 (-0.94, -0.89) attributable to smoking-related stroke in Saudi Arabia. The ASR of death fell absolutely by 28.48%, with AAPC of -1.08 (-1.11, -1.05) between 1990 and 2021. In contrast, the ASR of YLDs absolutely increased by 5.17% during the same period, with an APCC of 0.15 (0.14, 0.17). Further, the decline in AAPCs of ASR of DALYs (-1.99), ASR of YLLs (-1.79), and ASR of deaths (-1.90) was primarily influenced by the reduction in the female population, p < 0.001, except ASR of YLDs, where the increase in the AAPC was attributed to a rise in the male population, p < 0.001. In 2021, YLLs contributed 93% (157.81/179.02) of total DALYs from smoking-related strokes in Saudi Arabia. Death rates rose in all age groups in 2021, with the most significant increases seen in the younger and middle-aged groups (30-59 years). Conclusion While the rates of deaths, DALYs, and YLLs attributable to smoking-related stroke decreased in Saudi Arabia between 1990 and 2021, YLDs significantly increased, mainly in males during the same period. This emphasizes the need for targeted intervention focused mainly on the younger and middle-aged males.